Selection method of interlayer adhesive dosage and construction method of anti-delamination bridge deck pavement

By forming different structures of the carbine test parts with different structures in the bridge surface, and testing the adhesive dosage test, the optimal amount of adhesives of the bridge pavement layer are determined, solving the adhesion in existing technologies. The push and sectors of the bridge floor paving layer caused by the inappropriate dosage of the agent improved the quality of the bonding layer and the accuracy of the construction.

CN114509317BActive Publication Date: 2025-01-28SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210037299.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-13
Publication Date
2025-01-28
Estimated Expiration
2042-01-13

AI Technical Summary

Technical Problem

The existing bridge deck paving layer has problems such as transition and delamination caused by inappropriate amount of adhesive, and the determination of the amount of adhesive is not targeted, which can easily lead to poor bonding effect.

Method used

By forming different constructing depth test parts in the test model, the coating and testing of different amounts of binders in the square area is divided into a square area on its surface, combined with the minimum daily multiplication fitting adhesive and shear strength Relational curve to determine the best amount of adhesive at different structures.

Benefits of technology

The precise control of the amount of adhesives of the bridge pavement layer is realized, the quality of bonding the bonding layer is improved, the diseases such as pushing and dedue are prevented, and the cost of maintenance and maintenance of the later period is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114509317B_ABST
    Figure CN114509317B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for selecting the amount of interlayer adhesive and a method for anti-delamination bridge deck pavement construction, and uses experiments to determine different structural depths TD n The corresponding optimal binder dosage m n , fitting TD n ‑m n The relationship curve is used as the basis for selecting the optimal amount of adhesive between the pavement layers. After the paving of the lower layer is completed, the lower layer of the bridge deck pavement is shot blasted and its structural depth is measured by the sand paving method; when constructing the bonding layer, according to the structural depth of the lower layer of the bridge deck pavement, the TD n ‑m n The relationship curve is interpolated to determine the optimal amount of interlayer adhesive. The pavement structure of the present invention has good interlayer integrity and continuity, significantly improved interlayer bonding strength, and improved anti-delamination, anti-fatigue and water stability properties, which can effectively prevent bridge deck pavement displacement and delamination diseases and reduce operation and maintenance costs; the design method of the pavement structure is scientific and concise, the construction method has a high degree of mechanization, and the operation is simple and convenient, which can achieve the purpose of finely controlling the construction quality of the bonding layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for selecting the amount of an interlayer adhesive and a method for anti-delamination bridge deck paving construction, belonging to the technical field of road engineering. Background Art

[0002] With the continuous optimization of bridge deck pavement structure design and the continuous improvement of design theory, a bridge deck pavement composite structure system represented by a double-layer asphalt concrete pavement structure has gradually been formed, which gives full play to the excellent performance of the upper and lower pavement materials and makes the overall force more reasonable. The key to the double-layer pavement system is that the upper and lower pavement layers must be firmly bonded to form a whole, but in the actual service process, the asphalt pavement layer is often prone to failure of the bonding layer due to insufficient bonding strength under the action of vehicle loads, which in turn causes the bridge deck pavement to shift, delamination and other diseases, which not only increases the cost of later maintenance, but also reduces the expected service life of the bridge deck pavement.

[0003] The amount of adhesive material has a significant impact on the interlayer bonding performance of the pavement layer. If the amount of adhesive is too small, the interlayer bonding effect cannot meet the actual use requirements and delamination is likely to occur; if the amount of adhesive is too large, the cost will increase significantly, and the adhesive material will accumulate and flow on the surface, affecting the bonding quality of the bonding layer, burying a major hidden danger to the quality of the bridge deck pavement. At present, the amount of adhesive material used in the interlayer of the pavement is often determined by empirical values, that is, the determination of the amount of interlayer adhesive during construction does not consider the surface state of the layers below the pavement, but directly takes the value within the given empirical value range, which lacks pertinence and is prone to poor bonding of the bonding layer due to inappropriate adhesive dosage. When different paving materials and rolling processes are used in the lower layer of the bridge deck pavement, the structural depth is significantly different, so the amount of interlayer adhesive will also change due to the change in the structural depth of the lower layer of the pavement. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for selecting the amount of adhesive between layers of anti-delamination bridge deck pavement and a construction method, which can effectively solve the problems of pavement shifting, delamination and other defects caused by pollution and poor adhesive dosage of existing bridge deck pavement. The anti-delamination bridge deck pavement structure design and construction method have simple operation steps, and are easy to accurately control the amount of adhesive between bridge deck pavement layers and the construction quality, effectively improving the bonding quality between pavement bonding layers; the scope of use is wide, and it is particularly suitable for the construction of interlayer bonding layers of bridge deck pavement and road pavement.

[0005] Technical solution: A method for selecting the amount of interlayer adhesive for anti-delamination bridge deck pavement, comprising the following steps:

[0006] (1) According to the production mix ratio of epoxy asphalt EA10 for the lower layer of bridge deck pavement, EA10 rutting plate specimens were formed in the test mold by wheel rolling method; by controlling the number of rolling passes and combining shot blasting with shot blasting machine, rutting plate specimens of 7 structural depths were formed in sequence, with 3 rutting plate specimens for each structural depth;

[0007] (2) After all the rutting plate specimens in step (1) have been fully cured, demolding is performed and loose particles on the surface of the specimens are brushed off with a brush, and the upper surface of each rutting plate specimen is divided into three equal parts by length and width, and divided into 9 square areas;

[0008] (3) taking 9 different amounts of adhesives, and applying the 9 different amounts of adhesives to 9 square areas on the upper surface of each rutting board specimen in step (2); marking the amount of adhesive applied in each square area of ​​the rutting board specimen coated with the adhesive and curing at 25° C. for 48 h;

[0009] (4) Using the rutting plate specimen in step (3) as the lower pavement layer, the surface coated with the adhesive is placed upward in the rutting plate test mold, and then the rutting plate test mold is placed in the wheel rolling instrument; on the rutting plate specimen coated with the adhesive, the production mix ratio of the asphalt mixture SMA13 for the upper pavement layer is used, and the SMA13 upper pavement layer is formed by the wheel rolling method again. After the rutting plate specimen is completely cooled, the entire rutting plate specimen is demolded, and the upper surface of the demolded rutting plate specimen is divided into three equal parts in length and width, and divided into 9 square areas to facilitate subsequent cutting along the lines drawn on the surface;

[0010] (5) Using a cutting machine, cut the wheel rutting plate specimen in step (4) into 9 equal cubic specimens according to the pre-marked lines, and use them as shear specimens for later use;

[0011] (6) After the shear specimens in step (5) are dried, they are placed at a constant temperature of 25° C. for 6 h, and then a shear test is performed: the shear strengths of the shear specimens corresponding to 9 different adhesive dosages at different structural depths are measured in sequence, and the average of the test results of the shear specimens with the same adhesive dosage is taken as the shear strength corresponding to each adhesive dosage;

[0012] (7) At different structural depths, the relationship curve between the amount of binder and the shear strength was fitted by the least square method, and the maximum shear strength and the corresponding amount of binder were found according to the relationship curve between the amount of binder and the shear strength, which is the optimal amount of binder at different structural depths;

[0013] (8) Based on the optimal amount of binder at different construction depths in step (7), the relationship curve between the construction depth and the optimal amount of binder is fitted using the least squares method, which serves as the basis for selecting the optimal amount of binder between pavement layers.

[0014] Furthermore, the adhesive is an epoxy resin adhesive.

[0015] Furthermore, the shear test is performed using a universal testing machine UTM.

[0016] A construction method for an anti-delamination bridge deck pavement structure comprises the following steps:

[0017] (A) After the lower layer EA10 of the bridge deck is paved and cured, the bridge deck is divided into sections: each lane is divided into sections at set intervals along the length direction of the bridge deck;

[0018] (B) After step (A) is completed, the lower layer of the bridge deck pavement is shot blasted using a shot blasting machine;

[0019] (C) After step (B), three points are randomly selected in each interval, and the structural depth of each point is measured in turn using the sand spreading method, and the average of the three structural depths is taken as the structural depth of the interval;

[0020] (D) for the interval in step (C) where the construction depth is less than the set threshold, use a hand-push shot blasting machine to perform shot blasting until the construction depth is not less than the set threshold, and use the method of step (C) to update the construction depth of the interval;

[0021] (E) After step (D) is completed, the structural depth of each interval of the lower layer of the bridge deck pavement is sorted from small to large, and the structural depth of the 75% percentile value is taken as the structural depth of the lower layer of the bridge deck pavement;

[0022] (F) determining the optimum amount of adhesive between the bridge deck pavement layers by interpolation based on the relationship curve between the construction depth and the optimum amount of adhesive obtained by the method described above;

[0023] (G) According to the best binder determined in step (F), an asphalt spreader is used to spread the binder between the bridge deck pavement layers. After the spreading construction is completed, traffic is closed and sufficient curing is carried out. After the curing is completed, the top layer SMA13 is constructed.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0025] (1) The amount of adhesive used between the pavement layers takes into account the actual structural depth of the pavement layer below. That is, the actual structural depth of the pavement layer below the pavement is measured by manual sand laying method. n -m n Relationship curve to determine the optimum amount of interlayer adhesive m nThe determination of the amount of adhesive is more accurate and quick, which is in line with the actual situation of bridge deck paving. The value is objective, targeted and definite, which can effectively prevent the situation where too little or too much adhesive leads to poor bonding effect and increased maintenance costs in the later stage.

[0026] (2) Shot blasting is performed on the lower layer of the bridge deck pavement to completely eliminate wheel marks and dust pollution on the lower layer of the bridge deck pavement, effectively improve the texture structure of the lower layer of the bridge deck, and make the structural depth more uniform and consistent. It can also be based on TD n -m n The ideal construction depth is determined in advance by the relationship curve, and then the pavement layer is shot blasted to the ideal construction depth using a shot blasting machine, etc., to achieve the purpose of finely controlling the construction quality of the bonding layer;

[0027] (3) The present invention is not limited to determining the amount of adhesive between bridge deck pavement layers, but is also applicable to determining the amount of adhesive between ordinary asphalt pavement layers, and has good universality. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The lower layer S of the bridge deck pavement in the present invention ij Schematic diagram of interval division;

[0029] Figure 2 is the amount of binder used when TD2 = 0.7 mm in the present invention. nk and shear strength τ nk Schematic diagram of the relationship curve;

[0030] Figure 3 The depth TD constructed in the present invention n Optimal amount of binder n Schematic diagram of the relationship curve;

[0031] Figure 4 It is a flow chart of the construction method in the present invention. DETAILED DESCRIPTION

[0032] The following is a further detailed description of the features of the present invention and other related features through implementation example 1 and implementation example 2 in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the implementation examples.

[0033] Example 1

[0034] The lower pavement of a newly built bridge deck uses 4cmEA10, and the upper pavement uses 4cmSMA13. In order to ensure the uniform and stable performance of the interlayer bonding layer of the bridge deck pavement, and to prevent the occurrence of interlayer shifting, delamination and other diseases due to the pollution of the lower pavement layer and the unreasonable amount of adhesive, the epoxy resin adhesive is now used as the interlayer bonding material of the bridge deck pavement to design and construct the anti-delamination bridge deck pavement structure.

[0035] The method for selecting the amount of interlayer adhesive for the anti-delamination bridge deck pavement layer of this embodiment specifically includes the following steps:

[0036] (1) According to the production mix ratio of the lower layer of bridge deck pavement EA10, the wheel rolling method was used to form EA10 rutting plate specimens in a test mold with a length × width × height = 300 mm × 300 mm × 50 mm. By controlling the number of rolling times and combining shot blasting with a shot blasting machine, three rutting plate specimens of seven structural depths were formed in turn.

[0037] (2) Measure the structural depths of the 21 rutting plate specimens in step (1) and mark them. Then sort them into 7 groups in ascending order of structural depth. Each group contains 3 rutting plate specimens with the same structural depth. The structural depth is recorded as TD. n , where TD n is the construction depth of the nth group of rutting plate specimens, and n is an integer between [1,7]. After sufficient curing, all rutting plate specimens are demoulded and the loose particles on the surface of the specimens are brushed off with a brush. The upper surface of each rutting plate specimen is divided into 9 square areas of 100mm×100mm by drawing lines in terms of length and width into three equal parts.

[0038] (3) The experiment used 9 different amounts of binder, and ranked them in order from small to large, denoted as m nk , m nk is the amount of the kth binder used for the nth group of rutting plate specimens, n is an integer between [1,7], and k is an integer between [1,9]. Take the nth group of rutting plate specimens in step (2), that is, the construction depth TD n The rutting plate specimens were mixed with 9 different dosages m nk The adhesives were respectively applied to the 9 divided square areas on the surface of each rutting board specimen, that is, each amount of adhesive corresponded to a square area on the rutting board specimen, until the adhesive coating on the surfaces of the 3 rutting board specimens of the nth group was completed; the amount of adhesive in each square area of ​​the rutting board specimens coated with adhesive was marked and cured at 25°C for 48 hours.

[0039] (4) The rutting plate specimen in step (3) is used as the lower pavement layer, and the surface coated with the adhesive is placed upward in a test mold of length × width × height = 300mm × 300mm × 100mm, and then the test mold is placed in a wheel rolling machine; the wheel rolling method is used again on the rutting plate specimen coated with the adhesive to roll and form a SMA13 paving upper layer of length × width × height = 300mm × 300mm × 50mm thick according to the production mix ratio of the paving upper layer SMA13, and the specimen is demolded as a whole after it is completely cooled, and the upper surface of the rutting plate specimen of length × width × height = 300mm × 300mm × 100mm obtained by demolding is divided into three equal parts in length and width, that is, the specimen is divided into 9 square areas of 100mm × 100mm, so as to facilitate subsequent cutting along the lines drawn on the surface.

[0040] (5) Use a cutting machine to cut the wheel rutting plate specimen of length × width × height = 300 mm × 300 mm × 100 mm in step (4) into 9 equal parts according to the pre-marked lines, i.e., cubic specimens of length × width × height = 100 mm × 100 mm × 100 mm, as specimens for the shear test; this process is repeated until the same structural depth TD is reached. n After all three rutting plate specimens are cut, the structural depth TD can be obtained. n Three shear specimens corresponding to each binder dosage under the same conditions.

[0041] (6) After the shear test piece in step (5) is dried, it is placed at a constant temperature of 25°C for 6 hours, and then a shear test is performed: the shear test pieces at the structural depth TD are measured in turn. n 9 different binder dosages under different conditions nk The shear strength of the corresponding shear specimen is the average of the test results of three shear specimens with the same adhesive dosage as the shear strength τ corresponding to each adhesive dosage. nk , that is, τ nk Construct depth TD for group n n The average shear strength of the rutting plate specimen under the kth binder dosage condition. Taking TD2 as an example, as shown in Table 1, the shear strength of different binder dosages under TD2 = 0.7 mm.

[0042] Table 1 Shear strength of different adhesive dosages under the condition of structural depth TD2 = 0.7 mm

[0043]

[0044] (7) At the construction depth TD n Under the conditions, the least square method is used to fit the binder dosage m nk and shear strength τ nk The relationship curve m nk -τ nk , and according to mnk -τ nk The relationship curve finds the maximum shear strength τ nk And the corresponding binder dosage m n , m n That is the construction depth TD n The optimal amount of binder when. Take TD2 as an example, Figure 2 The amount of binder shown is m nk and shear strength τ nk relationship curve.

[0045] (8) Replace the next set of rutting plate specimens with the next structural depth, and repeat steps (3), (4), (5), (6) and (7) until 7 sets of rutting plate specimens with different structural depths TD in step (2) are obtained. n The optimal adhesive coating amount m corresponding to the rutting plate specimen n All confirmed.

[0046] (9) According to the different construction depths TD in step (8) n The corresponding optimum binder dosage m n , using the least squares method for TD n -m n Relationship curve fitting (such as Figure 3 The relationship curve is used as the basis for selecting the optimal amount of adhesive between pavement layers.

[0047] The anti-delamination bridge deck pavement structure construction method of this embodiment is as follows: Figure 4 As shown, the specific steps include:

[0048] (A) After the lower layer EA10 of the bridge deck is paved and cured, the bridge deck is divided into areas. The bridge deck is numbered according to the number of lanes along the width direction, and each lane is divided into sections every 5m along the length direction and numbered, denoted as S ij , that is, S ij It is represented as the jth interval of the i-th lane of the bridge deck, such as Figure 1 shown.

[0049] (B) After step (A), the lower layer of the bridge deck pavement is shot blasted 1 to 2 times using a shot blasting machine. The shot blasting should be carried out on a sunny day with an ambient temperature of not less than 10°C and an air relative humidity of not more than 80%, and with no wind or light wind. During construction, the power of the shot blasting machine is controlled at 1500 to 1800 r / min, the particle size of the steel shot used is 2 to 3 mm, the travel speed is controlled at 7.5 to 8.5 m / min, and the construction direction is from the longitudinal direction of the bridge along the low side to the high side. Each shot blasting overlaps the previous shot blasting construction width by 3.5 to 4.0 cm, and the adjacent shot blasting surfaces are kept parallel as much as possible. The structural depth of the pavement surface after shot blasting should be not less than 0.5 mm.

[0050] (C) After step (B), at each S ij Three points were randomly selected in the interval, and the structural depth was measured in sequence using the sand spreading method. The average value of these three structural depths was taken as the S ij The construction depth of the interval is recorded in the table.

[0051] (D) For S with a construction depth less than 0.5 mm in step (C), ij Use a hand-push shot blasting machine to blast the area until it is not less than 0.5 mm, measure the construction depth of the area again and update it in the record table of step (C).

[0052] (E) Count the number of S on the lower layer of the bridge deck after shot blasting. ij The construction depth values ​​of the interval are sorted from small to large, and the construction depth of the 75% percentile value is taken as the construction depth of the layer below the bridge deck pavement.

[0053] (F) According to the structural depth of the lower layer of the bridge deck pavement obtained in step (E), the TD of step (9) in the anti-delamination bridge deck pavement structure design method can be used. n -m n Relationship curve, interpolation to determine the optimal amount of adhesive between bridge deck pavement layers m n .

[0054] (G) The optimum binder m determined in step (F) n , use an asphalt spreader to spread the adhesive between the layers of the bridge deck pavement; after the spreading construction is completed, close the traffic and fully cure it, and after the curing is completed, proceed with the construction of the top layer SMA13.

[0055] Example 2

[0056] The bridge deck pavement structure in Example 2 is the same as that in Example 1 except that the 75% percentile structural depth of the lower pavement layer after shot blasting is different from that in Example 1 (see Table 2 for details). Other designs and construction methods are the same as those in Example 1.

[0057] The interlayer bonding performance test results of the bridge deck pavement layers of Example 1 and Example 2 are shown in Table 2:

[0058] Table 2 Test results of interlayer bonding performance of bridge deck pavement

[0059]

[0060] Note: The comparison example is a commonly used bridge deck pavement structure, with the lower layer being 4cmEA10 and the upper layer being 4cmSMA13.

[0061] In Table 2, the amount of interlayer adhesive used in Example 1 and Example 2 is based on the depth of the underlying layer structure using the TD n -m n The relationship curve is determined, and the value is objective and certain. The amount of interlayer adhesive in the comparative example is selected on the premise of meeting the technical requirements and combining with previous engineering experience, and it is subjective and arbitrary. It can be seen from the performance test results in Table 2 that the anti-delamination bridge deck pavement structure design and construction method disclosed in the present invention, compared with the previous bridge deck pavement structure, the pavement layer of the present invention has good integrity and continuity between layers, significantly improved bonding strength, and improved anti-delamination, anti-fatigue and water stability. The delamination disease caused by unreasonable amount of adhesive between the pavement layers of the bridge deck is effectively prevented, and the operation and maintenance cost is reduced. In addition, the construction of the anti-delamination bridge deck pavement structure and the method for determining the optimal amount of adhesive between the pavement layers have a high degree of mechanized construction, simple and convenient operation, strong feasibility, and can achieve the purpose of fine tracking and controlling the construction quality of the bonding layer.

[0062] The applicant declares: The present invention illustrates the detailed implementation method of the present invention through the above specific implementation methods, but the present invention is not limited to the above detailed implementation steps and methods. The technicians in the relevant technical field should understand that any modification or deformation of the present invention that does not require creative labor belongs to the protection scope and disclosure scope of the present invention. The above description is only used to help understand the method and core idea of ​​the present invention. Therefore, the content of this specification should not be understood as a limitation of the present invention.

Claims

1. A method for selecting the amount of interlayer adhesive for anti-delamination bridge deck pavement, characterized in that: The steps include: (1) According to the production mix ratio of epoxy asphalt EA10 for the lower layer of bridge deck pavement, EA10 rutting plate specimens were formed in the test mold by wheel rolling method; by controlling the number of rolling passes and combining shot blasting with shot blasting machine, rutting plate specimens of 7 structural depths were formed in sequence, with 3 rutting plate specimens for each structural depth; (2) After all the rutting plate specimens in step (1) have been fully cured, demolding is performed and loose particles on the surface of the specimens are brushed off with a brush, and the upper surface of each rutting plate specimen is divided into three equal parts by length and width, and divided into 9 square areas; (3) taking 9 different amounts of adhesives, and applying the 9 different amounts of adhesives to 9 square areas on the upper surface of each rutting plate specimen in step (2); marking the amount of adhesive applied to each square area of ​​the rutting plate specimen coated with the adhesive and curing the specimen at 25° C. for 48 h; (4) Using the rutting plate specimen in step (3) as the lower pavement layer, the surface coated with the adhesive is placed upward in the rutting plate test mold, and then the rutting plate test mold is placed in the wheel rolling instrument; the production mix ratio of the asphalt mixture SMA13 for the upper pavement layer is used on the rutting plate specimen coated with the adhesive, and the SMA13 upper pavement layer is formed by the wheel rolling method again. After the rutting plate specimen is completely cooled, the entire rutting plate specimen is demolded, and the upper surface of the demolded rutting plate specimen is divided into three equal parts in length and width, and divided into 9 square areas; (5) Using a cutting machine, cut the wheel rutting plate specimen in step (4) into 9 equal cubic specimens according to the pre-marked lines, and use them as shear specimens for later use; (6) After the shear specimens in step (5) are dried, they are placed at a constant temperature of 25° C. for 6 h, and then a shear test is performed: the shear strengths of the shear specimens corresponding to 9 different adhesive dosages at different structural depths are measured in sequence, and the average of the test results of the shear specimens with the same adhesive dosage is taken as the shear strength corresponding to each adhesive dosage; (7) At different structural depths, the relationship curve between the amount of binder and the shear strength was fitted by the least square method, and the maximum shear strength and the corresponding amount of binder were found according to the relationship curve between the amount of binder and the shear strength, which is the optimal amount of binder at different structural depths; (8) Based on the optimal amount of binder at different construction depths in step (7), the relationship curve between the construction depth and the optimal amount of binder is fitted using the least squares method, which serves as the basis for selecting the optimal amount of binder between pavement layers.

2. The method for selecting the amount of interlayer adhesive for anti-delamination bridge deck pavement according to claim 1, characterized in that: The adhesive is an epoxy resin adhesive.

3. The method for selecting the amount of interlayer adhesive for anti-delamination bridge deck pavement according to claim 1, characterized in that: The shear test was conducted using a universal testing machine UTM.

4. A construction method for an anti-delamination bridge deck pavement structure, characterized in that: The steps include: (A) After the lower layer EA10 of the bridge deck is paved and cured, the bridge deck is divided into sections: each lane is divided into sections at set intervals along the length direction of the bridge deck; (B) After step (A) is completed, the lower layer of the bridge deck pavement is shot blasted using a shot blasting machine; (C) After step (B), three points are randomly selected in each interval, and the structural depth of each point is measured in turn using the sand spreading method, and the average of the three structural depths is taken as the structural depth of the interval; (D) After step (C) is completed, the structural depth of each interval of the lower layer of the bridge deck pavement is sorted from small to large, and the structural depth of the 75% percentile value is taken as the structural depth of the lower layer of the bridge deck pavement; (E) determining the optimum amount of adhesive between the bridge deck pavement layers according to the relationship curve between the construction depth and the optimum amount of adhesive obtained by the method as claimed in any one of claims 1 to 3; (F) According to the best binder determined in step (E), an asphalt spreader is used to spread the binder between the bridge deck pavement layers. After the spreading construction is completed, traffic is closed and sufficient curing is carried out. After the curing is completed, the top layer SMA13 is constructed.

5. The construction method of an anti-delamination bridge deck pavement structure according to claim 4, characterized in that: In step (B), the shot blasting treatment is performed in a sunny day with an ambient temperature of not less than 10°C and an air relative humidity of not more than 80%, and in windless or breezy weather; during construction, the power of the shot blasting machine is controlled at 1500-1800r / min, the particle size of the steel shot used is 2-3mm, the travel speed is controlled at 7.5-8.5m / min, and the construction direction is from the longitudinal bridge along the low side to the high side in sequence. Each shot blasting overlaps the previous shot blasting construction width by 3.5-4.0cm, and the adjacent shot blasting surfaces are kept parallel. The structural depth of the pavement surface after shot blasting is not less than 0.5mm.

6. The construction method of an anti-delamination bridge deck pavement structure according to claim 4, characterized in that: The method also includes using a hand-propelled shot blasting machine to perform shot blasting on the interval in step (C) where the structural depth is less than a set threshold until the structural depth is not less than the set threshold, and using the method of step (C) to update the structural depth of the interval.

7. The construction method of an anti-delamination bridge deck pavement structure according to claim 6, characterized in that: Set the threshold to 0.5mm.

Citation Information

Patent Citations

  • Polymer asphalt based waterproof adhesive material and preparation process and construction process thereof

    CN102746822A

  • Method for determining optimum napping process parameters of new and old asphalt contact surface

    CN104048877A